Production of antibiotics via Genetic engineering applications / A Review Article - Dr.Ali R. Laftah; Dr. Azal hamody jumaa; Dr. Abdalkader Saeed Latif; Dr.Noor Naji Ajmi; Sura Mehdi Munshid (Peerian Journals Publishing, 2024)
Genetic engineering techniques are evolving, increasing the prospect of altering microorganisms to generate antibiotics more effectively. This article will showcase some of the successful implementations of these strategies, with a focus on the quantitative and qualitative gains in antibiotic production. It also discusses the obstacles facing this field and how to overcome them in order to create sustainable and effective antibiotic production, which has resulted in significant changes in many sectors of the modern economy, particularly agriculture and its dependent businesses. Industrial fermentation, the employment of free and bound enzymes and attracted
Keywords: Biotechnology; Genetic Engineering; Microbiology